Discovery of the genus Plethodontohyla (Anura: Microhylidae) in dry western Madagascar: description of a new species and biogeographic implications - Glaw, Frank; Köhler, Jörn; Bora, Parfait; Rabibisoa, Nirhy H.c.; Ramilijaona, Olga; Vences, Miguel (Zootaxa, 2007)
The cophyline anuran genus Plethodontohyla is considered to be restricted to humid eastern and central Madagascar. Recent surveys of the herpetofauna in the karstic limestone massif "Tsingy de Bemaraha" revealed a distinctive new species which constitutes the first record of this genus in central-western Madagascar. Plethodontohyla fonetana sp. nov. is characterized by large size (snout-vent length up to 65 mm in females), enlarged fingertips, sinuous dorsal folds, and a reticulated dorsal coloration. It is probably closely related to the other Plethodontohyla species with enlarged fingertips. The discovery of the new species suggests the existence of forest corridor between the eastern rainforest stretch and the relatively dry Tsingy de Bemaraha massif during a period of more humid climate. A continuous strip of gallery forest along a river running from the central high plateau to the west might have been sufficient to allow dispersal to the Bemaraha plateau.